2008
DOI: 10.1016/s1726-4901(08)70088-1
|View full text |Cite
|
Sign up to set email alerts
|

Luteal Support for IVF/ICSI Cycles with Crinone 8% (90 mg) Twice Daily Results in Higher Pregnancy Rates Than with Intramuscular Progesterone

Abstract: The use of vaginal progesterone gel twice daily for luteal support results in better pregnancy outcomes than intramuscular progesterone. A high local progesterone effect from vaginal gel might improve endometrial receptivity under extraordinarily high serum estradiol levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…In a retrospective study, patients who underwent assisted reproductive cycles using PVG twice daily were compared with patients receiving IMP 50 mg daily as luteal support. It was concluded that the ongoing pregnancy rate and implantation rate were significantly higher for the vaginal gel two times a day regimen compared with IMP (15). However, in our study, we could not find any statistically significant difference in clinical outcomes between the two groups of patients undergoing antagonist cycles.…”
contrasting
confidence: 84%
“…In a retrospective study, patients who underwent assisted reproductive cycles using PVG twice daily were compared with patients receiving IMP 50 mg daily as luteal support. It was concluded that the ongoing pregnancy rate and implantation rate were significantly higher for the vaginal gel two times a day regimen compared with IMP (15). However, in our study, we could not find any statistically significant difference in clinical outcomes between the two groups of patients undergoing antagonist cycles.…”
contrasting
confidence: 84%
“…One study (26) was a small matched control study that included the 90 mg bioadhesive gel every day regimen as well as two regimens of the vaginal tablet (Endometrin; Ferring Pharmaceuticals, Parsippany, NJ), which were combined as ''vaginal P '' and compared with a matched control group of IM P. The reported outcomes were comparable between the vaginal and IM routes of LPS (26). In a retrospective study, IVF and intracytoplasmic sperm injection patients receiving 90 mg bioadhesive gel administered two times a day was compared with patients receiving IM P (27). In that study the pregnancy outcomes were significantly higher for the vaginal bioadhesive gel two times a day compared with IM P. Studies of pregnancy outcomes in donor oocyte cycles (donor) and frozen embryo transfer cycles (FET) comparing vaginal P dosing to IM P dosing have most frequently compared the 90 mg bioadhesive gel two times a day to IM P. Four studies confirm that vaginal dosing is comparable to IM dosing (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been a viewpoint projected that measuring serum progesterone for adequacy of pessary dosage and effect is irrelevant, as pessaries placed in the vagina somehow act directly on the endometrium, initially described as the first uterine pass effect (Bulletti et al, 1997), where radioactive (tritiated) progesterone was shown to travel from vagina to uterus in cadaveric specimens. Consequently, several clinical groups view vaginal administration of progesterone as superior to other routes (Ho et al, 2008;Manno et al, 2005;Tavaniotou et al, 2000). Conversely, a recent investigation has demonstrated that vaginal gel and intramuscular injection of progesterone showed comparable implantation and pregnancy rates in IVF patients receiving vitrified blastocysts (Shapiro et al, 2014).…”
Section: Figurementioning
confidence: 99%